DAMPAK PENDIDIKAN AGAMA KRISTEN TERHADAP SIKAP TOLERANSI DAN KEPEDULIAN SOSIAL SISWA - Mariyanti Adu; Yandry Diana Dethan; Fransiska Y Nggeong; Catur Prio Purnomo; Runita Charolin Hekneno (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
The influence of Christian religious education needs to be considered, because the approach and curriculum in the lesson can influence students' perceptions and attitudes towards cultural and religious diversity. Through Christian religious education, it can contribute to the character of social concern and the attitude of tolerance of students in schools. The method used is a quantitative approach. The research instrument is a questionnaire that meets the requirements for validity and reliability using a 1-5 Likert scale model. Data analysis used a simple linear regression analysis test and the coefficient of determination (R square) at an alpha significance level of 0.05 using SPSS version 16.01 for Windows. Based on data analysis in the first hypothesis, it is significant at 0.001 < 0.05 and the magnitude of the influence (R square) is 0.171, and in the second hypothesis it is significant at the figure 0.000 < 0.05 and the magnitude of the influence (R square) is 0.338. The research results concluded that there is a significant influence between Christian religious education on attitudes of tolerance, and there is a significant influence between Christian religious education and cocial concern.